The Impact of Lifestyle Factors on the Human Microbiome - Arif Rachman (Medical Studies and Health Journal (SEHAT), 2024)
The conclusions of this study highlight the complexity of the relationship between lifestyle and human microbiome composition, which is based on the results of a systematic literature review. Findings from the literature show that lifestyle factors such as diet, physical activity, and sleep habits have a significant impact on the composition and diversity of the human microbiome, both in the digestive system, skin, and oral cavity. These factors interact and influence each other, forming a complex network of relationships that influence the health and balance of the human microbiome. The implications of these findings are very important in the context of preventing and treating various microbiome-related diseases, such as obesity, diabetes, and inflammatory bowel disease. By understanding the relationship between lifestyle and the human microbiome, we can develop more effective and targeted intervention strategies, both in terms of behavior change and the development of therapies focused on modulating the microbiome. For future research, it is recommended to further explore the mechanisms underlying the interaction between lifestyle and the human microbiome, and involve more comprehensive and longitudinal analysis.